2007
DOI: 10.1007/s10350-007-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Attitudes Toward Medical Students in an Outpatient Colorectal Surgery Clinic

Abstract: Students are generally accepted in outpatient colorectal clinics (81 percent). Reasons for acceptance of students included being able to contribute to the teaching of future doctors. Reasons for refusal included perceived increased length of the office visit and patient privacy. We noticed significant differences in compliance by gender, race, and severity of disease, but not age, patient level of income, or education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 10 publications
3
21
1
1
Order By: Relevance
“…Of great interest in this work is that differences in attitudes were not only related to the sex of the patients but was also related to their educational level and socio-economic characteristics, which were evident even after stratifying for patient sex. This is contrary to the study of Shah-Khan and colleagues in Chicago that found no relationship between the economic level or degree of educational attainment and the degree of satisfaction of patients [31]. …”
Section: Discussioncontrasting
confidence: 97%
“…Of great interest in this work is that differences in attitudes were not only related to the sex of the patients but was also related to their educational level and socio-economic characteristics, which were evident even after stratifying for patient sex. This is contrary to the study of Shah-Khan and colleagues in Chicago that found no relationship between the economic level or degree of educational attainment and the degree of satisfaction of patients [31]. …”
Section: Discussioncontrasting
confidence: 97%
“…This survey has shown that 71% of patients would allow medical students to be present. This result agrees with previous research that reveals a general trend of acceptance amongst patients for medical student involvement 17…”
Section: Discussionsupporting
confidence: 93%
“…However conflict can arise between the educational requirements of medical students and the needs of the patients. Previous studies have shown that patients are generally tolerant of medical students in a variety of settings from the emergency department1 to outpatient clinics 27. However, no study has yet enquired about the acceptability of medical students during the induction of regional anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Em trabalho semelhante ao nosso estudo, também realizado em ambulatório de coloproctologia, porém com a presença de estudantes de medicina ao invés de residentes, obtiveram como maiores causas de recusa da presença dos estudantes, a perda de privacidade e o aumento do tempo da consulta 3 . Esta última razão não foi assinalada por nenhum paciente no presente estudo.…”
Section: Tabela 2 -Razões Para a Aceitação Da Presença Do Residente Dunclassified